Exploring the role of physical prototypes during co-creation activities at LEGO company using case study validation. Issue 3 (3rd July 2021) - Isa, Siti Salwa; Liem, Andre
ABSTRACT: This study explores the application of physical prototypes to facilitate co-creation activities involving different stakeholders through a case-study analysis. It investigates how physical prototypes support the work of LEGO team at PG2 Front End Design Department (PG2FEDD) in co-creation processes. Additionally, this study will enhance our understanding of how physical prototypes facilitate not only knowledge sharing but also anticipating future user needs. Moreover, the study illustrates how careful deliberation and selection of 'prototypes in the broadest sense' improve co-creation practices. Results indicate that LEGO applies low- and high-fidelity physical prototypes iteratively in divergent and convergent co-creation activities to gather constructive and emphatic feedback from the stakeholders. The success of their co-creation processes is due to the strength and distinctive qualities of the LEGO system empowering people to build and foster connection and collaboration.